Apolipoprotein E Gene Polymorphism Effects on Lipid Metabolism and Risk of Cerebral Infarction in Northwest Han Chinese Population - Wang Y; Yang S; Zhang S; Lu X; Ma W (Dove Medical Press, 2023)
Yaqi Wang,1,* Shuang Yang,1,* Suya Zhang,1,* Xiaoyu Lu,2 Wenbing Ma1,2 1Department of Pharmacology, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, Shaanxi, 710061, People's Republic of China; 2Department of Biological Science and Bioengineering, Key Laboratory of Biomedical Information Engineering of the Ministry of Education, School of Life Science and Technology, Xi'an Jiaotong University, Xi'an, Shaanxi, 710049, People's Republic of China*These authors contributed equally to this workCorrespondence: Wenbing Ma, Department of Pharmacology, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, Shaanxi, 710061, People's Republic of China, Tel/Fax +86-29-85323240, Email mawenbing@mail.xjtu.edu.cnBackground: The apolipoprotein E (ApoE) genetic variation may contribute to the development of Cerebral Infarction (CI). Serum lipid levels are known risk factors for CI, but the effect of the ApoE gene polymorphism on lipid metabolism remains unclear. This retrospective cohort study was designed to determine the role of ApoE genotypes in CI risk and the relationships between ApoE gene polymorphism and serum lipid levels among the population of northwest China.Patients and Methods: 517 CI patients and 517 non-CI controls were enrolled in the study. Polymerase chain reaction and hybridization were utilized to determine the ApoE gene polymorphisms.Results: The ϵ3/ϵ4 genotype and ϵ4 allele frequency were significantly higher in CI patients than in controls. When stratified by age and sex, statistically significant differences in the distribution and frequency of the ϵ3/ϵ4 genotype and ϵ4 allele were found between patients and controls. Compared to ϵ2 carriers, ϵ4 carriers had significantly lower ApoE levels and higher low-density lipoprotein cholesterol (LDL-C), ApoB and ApoB/ApoA-I levels in both two groups. Additionally, control participants with ϵ4 carriers had significantly higher levels of lipoprotein and total cholesterol (TC) levels than ϵ2 carriers, while CI patients with ϵ4 carriers had a significantly lower level of ApoA-I. After adjusting for other established risk factors, drinking, hypertension, lipoprotein, triglycerides (TG) and ϵ4 allele were significant independent risk factors for CI, which was shown to be associated with a nearly two-fold CI risk.Conclusion: This study demonstrated that ϵ4 allele is independent risk factors for CI among patients in Northwest China. ApoE polymorphism was associated with CI, which was partly mediated through blood lipids and may also be mediated through non-lipid pathways. These data might be of great clinical significance in individualized preventive and therapeutic strategies.Keywords: apolipoprotein E, cerebral infarction, gene polymorphism, Northwest China